Towards a Deeper Understanding of the Graduate Student and Faculty-Advisor Relationship - Chukwu, Smart; Walker, Keith D. (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2023)
The relationship between graduate students and faculty members is a topic of great interest in higher education. While there is a wealth of theoretical and empirical research on the subject, discussions overlook the social dynamics that shape these relationships. This article seeks to fill this gap by presenting a conceptual framework that considers crucial components, including interpretations, reciprocal roles and responsibilities, relational factors, and effects, in analysing graduate student-faculty advisor relationships. By exploring these elements, the article offers a comprehensive framework that accounts for the nuances and limitations of these relationships and provides recommendations for best practices.